Why all the fuss about randomised trials? - Chalmers, H (John Catt Educational, 2019)
Hamish Chalmers is a teacher and a lecturer in applied linguistics at the University of Oxford. Here he demystifies the opportunities and challenges that randomised controlled trials – RCTs – offer education and the classroom. They are often seen as a gold standard in research, and being aware of the differences between these qualities is essential to appreciating their value.